Identifikasi Telur Soil Transmitted Helminths Pada Caisim (Brassica chinensis) di Pasar Patikraja Kabupaten Banyumas - Nurul Qomariyah; Dita Pratiwi Kusuma Wardani; Retno Sulistiyowati (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2021)
Caisim (Brassica chinensis) is one of the vegetables that has many benefits such as protein, carbohydrates, fat and plays an important role in meeting food needs, and is good for health. Caisim is well adapted to high temperatures and the price is relatively stable and easy to cultivate. The purpose of this study was to determine the presence of Soil-Transmitted Helminths eggs in caisim (B. chinensis). The research was conducted in a descriptive observational. The research was conducted in July-August 2020 at Parasitology and Microbiology Laboratory, Faculty of Medicine, Universitas Muhammadiyah Purwokerto. Identification of Soil-Transmitted Helminths eggs from 20 caisim as the samples used NaCl flotation method and were analyzed by using a univariate test with tabulated frequency distribution. The results showed that no Soil-Transmitted Helminths eggs were found in caisim (B. chinensis).   Caisim (Brassica chinensis) merupakan sayuran yang mempunyai banyak kandungan manfaat seperti protein,karbohidrat, lemak dan berperan penting untuk memenuhi kebutuhan pangan serta baik untuk kesehatan. Caisimmampu beradaptasi dengan baik terhadap suhu tinggi serta harga relatif stabil dan mudah diusahakan. Tujuanpenelitian ini untuk mengetahui adanya telur Soil Transmitted Helminths terdapat pada caisim (B. chinensis).Penelitian dilakukan secara observasional deskriptif. Penelitian dilakukan pada bulan Juli-Agustus 2020 diLaboratorium Parasitologi Fakultas Kedokteran Universitas Muhammadiyah Purwokwerto. Identifikasi telur SoilTransmitted Helminthsdari 20 sampel caisim dengan metode Flotasi NaCl. dianalisis dengan uji univariat dengandistribusi tabulasi frekuensi. Hasil penelitian menunjukan tidak ditemukan telur Soil Transmitted Helminths padacaisim (B. chinensis)